Determinação dos metais pesados Cd, Cu, Cr e Pb nas águas do Rio Uberabinha e proposta de adsorção por adsorventes naturais - Bittar, Dayana Borges (2008)
Problems related to the pollution of rivers, streams, lakes and others, have been putting into discussion the indispensable urgency of attitude changes and proposing remediation methods to the hybrids bodies which supply the whole population of living beings. As Uberabinha River is a water source of vital importance to the region of Uberlândia/MG, this project has as its objective verifying its real conditions through physical [TDS, SS, color, turbidity, temperature) and chemical analyses (BOD, DO, metal concentration such as cadmium, (Cd), copper (Cu), chromium (Cr) and lead (Pb)]. Also, proposing a water remediation method which presents heavy metal concentrations Cd, Cu, Cr and Pb higher than the maximum value allowed by Normative Deliberation COPAM/CERH-MG 01/2008 by adsorption, with the help of natural adsorbents as Moringa oleifera and a clayish material, used for making bricks. The quantification rate of metals after the treatment with adsorbents was made by flame atomic absorption spectrometry (FAAS). With reference, a standard calibration curve for each metal was essential. After the heavy metal determination phase, solutions of the same ones were simulated and treated with the natural adsorbents moringa and clayish material, separated and respectively. To the adsorption test, in scads, an agitation by canting was initially accomplished varying the time of contact (10, 20, 30 and 40 minutes) and letting constant: pH, temperature, rotation speed, adsorbent concentration and mass. In a second moment, the mass of adsorbents was varied (10, 20, 30, 60 and 100 mg), where pH, temperature, volume, solution concentration, rotation speed and contact time remained constant. The results were quite satisfactory showing that the physical-chemical parameters were according to what law permits, except for the rate of heavy metals found in the river waters. To an adsorption, 10 mg of clayish material in a 10 minute contact time with metal solutions were sufficient to 100% of removal of the same ones. The moringa reached values close to the clay ones, except for Cd metal, showing that both adsorbents are very efficient in aid to decontamination of polluted waters by heavy metals, however, clay distinguished greatly.